Ethnic Behavior and Lifestyle of the Togutil Tribe in East Halmahera Regency, North Maluku - Bahrudin Hasan; Sihabudin Sihabudin; Jamalullail Jamalullail (International Journal of Education, Information Technology, and Others, 2021)
The purpose of this study was to find out the communication patterns that occurred between the Tugutil tribe and the local community that led to acculturation in East Halmahera Regency. The research approach used is qualitative research, which seeks to understand, explain and analyze the acculturation process between the Tugutil tribe and other ethnic communities in the "Gam Rangge" customary area of ​​East Halmahera Regency. The results showed that the occurrence of ethnic communication patterns of the Togutil tribe in carrying out cultural accurturation with the local community in East Halmahera was influenced by their cultural background which was still primitive, the life they lived while living in the forest always lived in groups and often moved from one place to another. somewhere else.